HUBUNGAN SIKAP, NORMA SUBJEKTIF, DAN PERCEIVED BEHAVIORAL CONTROL TERHADAP INTENSI BERHENTI MEROKOK MAHASISWA UPN VETERAN JAKARTA TAHUN 2022 - Qoriatuz Zaituni Fathiani (2022)
Smoking behavior has become a global problem including Indonesia. It's obliged to stop smoking in order to reduce the number of smokers and cigarette consumption. Through the concepts and models of The Theory of Planned Behavior. This study aims to determine the relationship between attitudes, subjective norms, and perceived behavioral control to the smoking cessation intention of UPN Veterans Jakarta students. This study used cross-sectional. The population were all UPN Veteran Jakarta students with 156 respondents taken by using purposive sampling technique. Data analysed using Chi-Square and multiple logistic regression. This study showed that 57.1% of students had strong intentions. Multivariate analysis showed that attitudes, subjective norms, and perceived behavioral control had an influence on the intention to quit smoking with the determinant having the greatest effect being attitude with a POR value = 5.731 (95% CI = 2.366-13.882). In conclusion, adolescents who have positive attitudes tend to be more likely to quit smoking. The student's desire to quit smoking is based on the student's assessment that quitting smoking is good and provides good things for him. Thus, students are expected to learn with people who have successfully quit smoking and explore information related to the benefits of quitting smoking.